2008
DOI: 10.1001/archderm.144.9.1129
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Collagen by Estradiol

Abstract: To evaluate the effectiveness of topical estradiol in stimulating collagen I and III production in naturally aged and photoaged human skin of postmenopausal women and age-matched men.Design: Vehicle-controlled treatment followed by biochemical and immunohistochemical analyses of skin biopsy specimens.Setting: Academic referral center.Participants: Seventy healthy volunteers (40 postmenopausal women with a mean age of 75 years, and 30 men with a mean age of 75 years) with photodamaged skin.Interventions: Topica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(17 citation statements)
references
References 59 publications
1
15
1
Order By: Relevance
“…As according to a recent study ERα represents a predominant isoform expressed in human dermal fibroblasts (Rittie et al ., 2008), we focused on this isoform and first confirmed its expression by reverse transcription-PCR (RT-PCR) (Figure 1a) and western blot (Figure 1b). MCF-7 breast cancer cells, which express full-length ERα, as well as 46 and 36 kDa splice variants (Flouriot et al ., 2000; Wang et al ., 2005), were used as a positive control.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…As according to a recent study ERα represents a predominant isoform expressed in human dermal fibroblasts (Rittie et al ., 2008), we focused on this isoform and first confirmed its expression by reverse transcription-PCR (RT-PCR) (Figure 1a) and western blot (Figure 1b). MCF-7 breast cancer cells, which express full-length ERα, as well as 46 and 36 kDa splice variants (Flouriot et al ., 2000; Wang et al ., 2005), were used as a positive control.…”
Section: Resultsmentioning
confidence: 89%
“…In this study we observed upregulation of ERα in response to TGF-β, suggesting that signaling through this receptor might be involved in the downstream effects of TGF-β, including ECM production in dermal fibroblasts. However, in spite of a large number of studies documenting stimulatory effects of topical estrogen on collagen accumulation in the skin (Rittie et al ., 2008), the mechanistic aspects of collagen gene regulation by estrogen remain poorly understood. Estrogen was also shown to induce collagen and other matrix proteins in cultured dermal fibroblasts (Surazynski et al ., 2003; Soldano et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IHC was performed as previously described (Rittié et al ., 2008), and slides were mounted with 90% glycerin or ProLong Gold medium (both from Thermo Fisher Scientific, Waltham, MA, USA). Imaging of horizontally cut sections was performed with a Leica MXFL III Stereo Microscope (Leica Microsystems, Buffalo Grove, IL, USA; accessed at the Microscopy and Image‐Analysis Laboratory, Biomedical Research Core Facilities, University of Michigan Medical School).…”
Section: Methodsmentioning
confidence: 99%
“…In particular in females in postmenopausal age, the blood concentrations of estrogen and progesterone drop considerably, and this is accompanied by the typical features of skin aging, i.e., dryness, epidermal atrophy, diminution of collagen, loss of elasticity, wrinkle formation, and impaired wound healing (Bolognia et al 1989 ;Brincat 2000 ;Rittie et al 2008 ;Sumino et al 2004 ). In particular in females in postmenopausal age, the blood concentrations of estrogen and progesterone drop considerably, and this is accompanied by the typical features of skin aging, i.e., dryness, epidermal atrophy, diminution of collagen, loss of elasticity, wrinkle formation, and impaired wound healing (Bolognia et al 1989 ;Brincat 2000 ;Rittie et al 2008 ;Sumino et al 2004 ).…”
Section: Estrogen Depletionmentioning
confidence: 99%